Pendampingan Literasi Lingkungan untuk Meningkatkan Kemampuan Tanggap Bencana Peserta Didik di SDN 013 Samarinda Kota - Ningrum, Mei Vita Romadon; Aisyah Trees Sandy; Yulian Widya Saputra (Education and Talent Development Center Indonesia, 2024)
This Community Service (PkM) activity was carried out at SDN 013 Kecamarinda Samarinda City, Samarinda City, East Kalimantan Province on May 7, 2024, which was attended by 30 students. The purpose this activities is to provide environmental literacy assistance in order to improve the disaster response ability of SDN 013 Samarinda Kota students. This mentoring activity is carried out through socialization and counseling methods with varied lecture strategies and through the delivery of disaster materials (especially flood disasters) and simple games. Based on the results of the activity, 83% of students said they could understand the material well and 89% of teachers answered that PKM activities were very helpful in implementing an understanding of the environment at school. The conclusion of this service activity is that it is carried out well in accordance with the expectations of the service team and the participants, where students are able to implement an understanding of environmental literacy on disaster response skills in schools and surrounding areas